2022
DOI: 10.3390/cancers14102454
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Comprehensive Genomic Profiling Tests for Diffuse Gliomas

Abstract: Next-generation sequencing-based comprehensive genomic profiling test (CGPT) enables clinicians and patients to access promising molecularly targeted therapeutic agents. Approximately 10% of patients who undergo CGPT receive an appropriate agent. However, its coverage of glioma patients is seldom reported. The aim of this study was to reveal the comprehensive results of CGPT in glioma patients in our institution, especially the clinical actionability. We analyzed the genomic aberrations, tumor mutation burden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The advantage of a comprehensive genomic profiling (CGP) test is the simultaneous analysis of the MSI status, genomic aberrations, and the TMB in solid tumors. A cohort study that used the F1CDx test for diffuse glioma reported that most of the glioblastoma indicated MSS despite a high TMB score [ 18 ]. However, another study demonstrated that the accuracy of an NGS-based MSI analysis is not perfect [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of a comprehensive genomic profiling (CGP) test is the simultaneous analysis of the MSI status, genomic aberrations, and the TMB in solid tumors. A cohort study that used the F1CDx test for diffuse glioma reported that most of the glioblastoma indicated MSS despite a high TMB score [ 18 ]. However, another study demonstrated that the accuracy of an NGS-based MSI analysis is not perfect [ 19 ].…”
Section: Discussionmentioning
confidence: 99%